1987
DOI: 10.1111/j.1559-1816.1987.tb00321.x
|View full text |Cite
|
Sign up to set email alerts
|

The Social Psychology of Caregiving: Physical and Psychological Costs of Providing Support to the Disabled1

Abstract: The emphasis of much of the existing research on social support‐health relationships has been on the availability and impact of support on the recipient, but social psychologists have paid little attention to the costs to the caregiver of providing that support. In an earlier study (Schulz & Decker, 1985), we found that the long‐term coping of individuals experiencing chronic disability as a result of spinal‐cord injury was facilitated by the availability of a primary support person, or caregiver. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 22 publications
1
74
1
1
Order By: Relevance
“…The mean psychological well-being score on the IPWB for the caregivers in this study were relatively high in reference to the suggested cutoff value of 3.77 for the general population, 14 and the mean scores of 3.91 for the caregivers of SCI persons. 16 This indicates that caregiving is a stressful experience. Depression, anxiety and poorer psychological well-being have been a common finding in studies evaluating the caregivers of SCI persons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean psychological well-being score on the IPWB for the caregivers in this study were relatively high in reference to the suggested cutoff value of 3.77 for the general population, 14 and the mean scores of 3.91 for the caregivers of SCI persons. 16 This indicates that caregiving is a stressful experience. Depression, anxiety and poorer psychological well-being have been a common finding in studies evaluating the caregivers of SCI persons.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with other studies, which have identified level of assistance provided in ADL and the number of hours spent providing support for the SCI person as strong contributors of caregiver burden. 16,19 However, there was no relationship between the caregiver burden and the time till which caregiving had been provided. Family support toward the care of the SCI persons was highly evident in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated before, most other studies have not used caregiver burden measures but used psychological distress and quality of life measures. Schulz et al 20 reported that the level of assistance provided in daily living activities and hours per day spent assisting the persons with SCI were strongly correlated with depression of caregivers. However, two studies in nonwestern countries, Turkey and South India, did not find significant relationships between severity of the injury or secondary conditions with caregiver's distress or quality of life.…”
Section: Carementioning
confidence: 99%
“…For this reason, it is not easy to interpret the sometimes conflicting results regarding the impact of severity of the injury, secondary conditions and the impact of duration of the injury. Unalan et al, 16 for example, found no correlation between the seriousness of the SCI and complications and caregivers' quality of life, whereas Schulz et al 20 reported that the amounts of assistance provided for the persons with SCI were strongly correlated with depression of caregivers. Further, most studies used small sample sizes 14,16,18 or used mixed samples of partners, other family members, nonfamily members or professional caregivers.…”
Section: Introductionmentioning
confidence: 99%